Oxidative stress in jobs with exposure to xenobiotics - Tavakol Heidari Shayesteh; Akram Ranjbar (طب کار)
Background: The terms Reactive Oxygen Intermediates or Reactive Oxygen Species (ROS) are used to describe the molecules as highly reactive oxygen molecules that will chemically oxidize neighboring susceptible molecules. A prominent feature of radicals is that they have extremely high chemical reactivity, which explains not only their normal biological activities, but how they inflict damage on cells. The free radical formation in a living system leads to oxidative damage of macromolecules, such as DNA, proteins and lipids. Oxidative stress is defined most simply as the imbalance between the production of free radicals and the body’s antioxidants. Epidemiological studies have provided evidence for an association between exposure to xenobiotics such as ambient polluted air particles, pesticides, metals, radiation and oxidative stress. Methods: Bibliographic databases including Scopus, PubMed and Google Scholar were searched between years 1960 to 2012 for the keywords "Oxidative stress" and jobs. In the first step, 17987 articles were found, after elimination of duplicates or irrelevant papers, 60 papers were selected and reviewed. Results: Sixty articles in this study have been used. Findings showed the relationship between jobs and oxidative stress. Conclusion: This review indicates that workers in various jobs are exposed to more oxidative stress damage. To overcome these oxidative stresses, supplementation with antioxidant vitamins, such as α-tocopherol and ascorbic acid, may have beneficial effects in these workers. It is reported that supplementation with antioxidants, protect against oxidative damage. Also, these workers need better precautions to protect them against serious health problem.